USP18 – a multifunctional component in the interferon response. Issue 6 (16th November 2018) - Basters, Anja; Knobeloch, Klaus-Peter; Fritz, Günter
Abstract : Ubiquitin-specific proteases (USPs) represent the largest family of deubiquitinating enzymes (DUB). These proteases cleave the isopeptide bond between ubiquitin and a lysine residue of a ubiquitin-modified protein. USP18 is a special member of the USP family as it only deconjugates the ubiquitin-like protein ISG15 (interferon-stimulated gene (ISG) 15) from target proteins but is not active towards ubiquitin. Independent of its protease activity, USP18 functions as a major negative regulator of the type I interferon response showing that USP18 is – at least – a bifunctional protein. In this review, we summarise our current knowledge of protease-dependent and -independent functions of USP18 and discuss the structural basis of its dual activity.